2015
DOI: 10.1152/ajpendo.00418.2014
|View full text |Cite
|
Sign up to set email alerts
|

Increased GIP signaling induces adipose inflammation via a HIF-1α-dependent pathway and impairs insulin sensitivity in mice

Abstract: Glucose-dependent insulinotropic polypeptide (GIP) is a gut hormone secreted in response to dietary fat and glucose. The blood GIP level is elevated in obesity and diabetes. GIP stimulates proinflammatory gene expression and impairs insulin sensitivity in cultured adipocytes. In obesity, hypoxia within adipose tissue can induce inflammation. The aims of this study were 1) to examine the proinflammatory effect of increased GIP signaling in adipose tissues in vivo and 2) to clarify the association between GIP an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
54
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 41 publications
7
54
1
4
Order By: Relevance
“…Thus, the net glycaemic effect of GIP is largely dependent on the balance of actions on both pancreatic α-and β-cells. Furthermore, evidence from rodent studies has linked GIP signalling to fat accumulation, adipose inflammation and weight gain, which may exacerbate insulin resistance (Chen et al 2014).…”
Section: Gipmentioning
confidence: 99%
“…Thus, the net glycaemic effect of GIP is largely dependent on the balance of actions on both pancreatic α-and β-cells. Furthermore, evidence from rodent studies has linked GIP signalling to fat accumulation, adipose inflammation and weight gain, which may exacerbate insulin resistance (Chen et al 2014).…”
Section: Gipmentioning
confidence: 99%
“…HIF-1α is involved in the transcriptional regulation of cytokines, such as IL-6 and TNF-α, during inflammation. 20, 21, 22 In addition, data suggest that HIF-1α expression can be induced by virus infection. 23, 24, 25, 26 However, the role of HIF-1α in H1N1 infection is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Previous in vitro studies have shown that GIP increases IL‐6 expression levels in adipose tissue. In astrocytes, CREB activated by β‐adrenergic receptor enhances IL‐6 expression induced by tumor necrosis factor (TNF)‐α receptor signaling.…”
Section: Gip Signaling In Adipose Tissuementioning
confidence: 99%